Implements Midtrans Payment Gateway for Digital Payments on the Hadirku Application - Mulyati Mulyati; Ahmad Herkal Taqyudin; Rini Septiowati; Kgomotso Moyo; Sularso Budilaksono (ADI Pengabdian Kepada Masyarakat, 2025)
The development of financial technology has driven the need for efficient, secure, and integrated digital payment systems within educational environments. However, the payment process for academic activities in the Hadirku Application at University of Raharja was previously conducted manually, often causing delays in payment confirmation and potential data entry errors. Through this community service program, a team of lecturers and students collaborated with the partner the administrators and users of the Hadirku Application to implement an automated payment system using the Midtrans Payment Gateway. The activities were carried out through several stages, including partner needs analysis, system design, API integration of Midtrans, and user training for both administrators and end users. The implementation results demonstrated a significant improvement in transaction efficiency. The average payment confirmation time, which previously took about two hours, has now been reduced to less than one minute through an automated process. In addition, the partner’s understanding of digital payment systems increased notably, and all transaction activities can now be monitored in real time through the Midtrans dashboard. This community service activity not only succeeded in automating the payment process within the Hadirku Application but also contributed to enhancing the digital literacy of the academic community and supporting the realization of a sustainable smart campus implementation at University of Raharja.